Transition to recycling versus incineration in municipal solid waste management : Evaluating the speed of greenhouse gas emission reduction - Zaikova, Anna; Falsafi, Amirmehrab; Falsafi, Amirsohrab; Abdulkareem, Mariam; Horttanainen, Mika (SAGE Publications, 2025)
With the urgent need for climate action, reducing landfill emissions is crucial. Motivated by potential differences in time required to transition from landfilling to recycling versus incineration of municipal solid waste (MSW), this study assesses which of the two pathways offers a quicker and more robust solution for mitigating greenhouse gas (GHG) emissions in MSW management. The speed of transition to waste incineration and recycling was analysed retrospectively among frontrunners in landfill reduction. In three selected cases, the speed of GHG emission reduction resulting from their transition mainly to waste incineration (Finland), recycling (Italy) and a combination of those (Poland) was calculated using life cycle assessment (LCA). Robustness of the results was tested by varying key parameters. The findings show that GHG emission reduction and its speed depend significantly on the energy sources being replaced on the market by energy derived from waste. Depending on trends in the energy market and how they are reflected in the LCA model, the effects of transitioning to incineration range from the largest and quickest GHG emission reductions to no environmental benefit. Taking into account the energy sector transition projections for various countries, potential cases were identified where transitioning to incineration can reduce GHG emissions faster than recycling. However, significant uncertainty arising from assumptions about the energy replaced, which was present even in retrospective analysis, highlights the need for robust solutions for emission reduction in future MSW management – solutions that can only be developed by comprehensively accounting for these uncertainties.
Keywords: landfill diversion; municipal solid waste; global warming potential; material recovery; waste-to-energy; speed; marginal data